1995
DOI: 10.2307/4002480
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Downy Brome to Nitrogen and Water

Abstract: Downy brome (Brooms tectorum L.) is an alien grass that dominates disturbed ground in shrub-steppe ecosystems of the western United States. Responses of downy brome to added nitrogen and water were evaluated using intact soil cores obtained from an old field. Gas exchange data were gathered at the leaf and canopy scales. Stomata1 conductance and net photosynthesis rates were greater at the leaf scale than at the canopy scale, decreased with time from germination, and were weakly affected by treatments. Water-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…As an annual species, cheatgrass generally has greater dependence on plant-available soil nutrients for successful establishment and persistence than perennial species (Marschner 1995). Past research has shown both soil nutrient concentration and native species competition to be important in regulating invasions (Link et al 1995;Booth et al 2003a;Chambers et al 2007); possibly their combined influences provided both community resiliency and resistance to cheatgrass invasion in our study.…”
Section: Invasion Resistance In the Native-dominated Communitymentioning
confidence: 86%
See 1 more Smart Citation
“…As an annual species, cheatgrass generally has greater dependence on plant-available soil nutrients for successful establishment and persistence than perennial species (Marschner 1995). Past research has shown both soil nutrient concentration and native species competition to be important in regulating invasions (Link et al 1995;Booth et al 2003a;Chambers et al 2007); possibly their combined influences provided both community resiliency and resistance to cheatgrass invasion in our study.…”
Section: Invasion Resistance In the Native-dominated Communitymentioning
confidence: 86%
“…Cheatgrass outcompetes many native perennial grass seedlings, but performs worse when competing with mature native plants (Booth et al 2003a;Lowe et al 2003;Humphrey and Schupp 2004). Furthermore, cheatgrass success is promoted by high soil nutrient levels, particularly nitrate, which often increases in the soil immediately after fire (Link et al 1995;Lowe et al 2003;Beckstead and Augspurger 2004;Gundale et al 2008).…”
Section: Introductionmentioning
confidence: 97%
“…The spread and success of B. tectorum in this region is thought to be due largely to disturbances in the form of grazing and increased fire frequency (Mack 1986;D'Antonio and Vitousek 1992;Mack et al 2000). In some cases, B. tectorum success has been linked to increases in nitrogen (N) (NPS 2000;Lowe et al 2003;Monaco et al 2003;Beckstead and Augspurger 2004) and water (Link et al 1995;Chambers et al 2007), but the nature of the response of B. tectorum to increasing levels of these resources is not known (e.g., linear, nonlinear or threshold dynamics).…”
Section: Introductionmentioning
confidence: 97%
“…However, we know little about the in situ patterns of photosynthesis for B. tectorum and the native herbaceous species at this site. Despite some greenhouse experiments (Dakheel et al, 1994;Link et al, 1995;Rice et al, 1992;Smith et al, 1987), we are not aware of any reports of the in situ patterns of photosynthesis for B. tectorum. Likewise, much of the research on B. tectorum has focused on invasions at lower elevations (Booth et al, 2003;Humphrey and Schupp, 2004;Mazzola et al, 2011;Rau et al, 2011), where impacts are extensive.…”
Section: Introductionmentioning
confidence: 98%